Oxford handbook of clinical specialties - Brinsden, Mark (Oxford University Press, 2006)
The seventh edition of this highly acclaimed Oxford Handbook covers all the major specialties not covered in its companion handbook, the Oxford Handbook of Clinical Medicine. It continues to provide all the ideas and facts essential to those who will or who are already caring for patientswhose needs may or may not fit within the traditional bounds of individual specialties. The text is concise and clear and laid out in the Oxford Handbooks' characteristic style of page-a-topic format, leaving space for the reader's own updatings and refinements.Updated throughout with extensive revisions in key chapters and all new colour illustrations, the text goes from stength to strength with every new edition. It is thoroughly up-to-date and more evidence-based than ever before. This pocket-sized book is brimming with practical advice and containshundreds of links to reliable medical internet sites such as Medline and Clinical Evidence, enabling the reader to probe deeper into the topics covered.Above all, the Oxford Handbook of Clinical Specialties remains human and humorous, and in this edition there is an increased emphasis on patient centred medicine. It provides not only the practical aspects of medical care, but also a philosophy of medicine which has come to be respected around theworld.